The ethical system and the media system: Reading in Contemporary cognitive trends - عبد الرحمن عزي (International Journal of Social Communication, 2018)
Abstract : The theory of value determinism in the media is both a scientific and a normative theory, providing a model of knowledge in the interpretation of the media phenomenon and its relationship to the levels of thought, mind and practice, looking at what should be, and has been preoccupied from the very beginning with the moral question of the media as a message despite the weight The means in contemporary society and by virtue of the attachment of value to the distinctive civilizational reference. The theoretical contribution of our study on media ethics is reflected in the Norism vision, which includes the "details " of the ethics that should be adopted in the media practice and the efforts made with the "Christens Clifford " In the context of what has become known as global media ethics